(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Patient satisfaction determines healthcare service effectiveness. Its extensive study can revealboth well-functioning problematic components of a hospital, making it an essential part of the qualityassessment. 375 patients admitted to the King Abdulaziz Medical City in Saudi were the focus of thisdescriptive cross-sectional study designed to gauge patient satisfaction identify contributing factors.Patients were chosen using non-random convenience sampling and were asked to fill out a validatedsurvey twice (in AugustSeptember and DecemberJanuary). The majority of respondents (50.8 percent)said they were happy with the study. Patients were more likely to be satisfied with their care overall ifthey were treated in the primary ED, admitting to the hospital first thing in the morning, attended the EDduring the off-season (Aug-Sept), and had shorter wait times to see a clinician.. The admission processgarnered the highest level of patient satisfaction, while the nursing care received the lowest.